Responsable Institutional Purchases (2013)
Our planet is in need of social responsibility. Recycle, recover and reuse are more than arranging the waste efficiently. Doing an effective source separation starting from the households, may be the first step in the process of recovering or recycling effectively. This is happening in Bogotá thanks to the good performance that has included environmental recyclers to the process in accordance with the judgment of the Constitutional Court C- 793 of 2009, conditional on the implementation of the environmental subpoena protecting the recyclers work. We are considering some thoughts about the challenges in organization and social inclusion that emerge while complying with Auto 275 of 2011 of the Constitutional Court which are part of the affirmative action made by the City Hall , headed by Special Administrative Unit of Public Service (UAESP) to incorporate recyclers in a new model of city cleanliness like other National and District institutions who will be part of the same affirmative action to comply with the Auto mentioned before from its mission as an institution trying to manage waste in a manner compatible with the environment, public health and social responsibility. Rearranging the public hygiene services towards utilization to encourage a process that incorporates in the public and private institutional purchases a percentage of goods produced with recycled raw material in the final stage of recycling.